Legal Policy Analysis Of Handling Covid-19 In The Perspective Of Human Rights Protection - Bambang Irawan, Benny; roto, Su; Setiawati, Sri (CV. Inara, 2022)
The Indonesian government has issued several regulations for the handling of Corona Virus Disease 2019 (Covid-19), which aims to handle the Covid-19 pandemic in Indonesia can run well and be adhered to by all communities. But the legal order issued by the Government of Indonesia in dealing with Covid-19 and the implementation of physical distancing has not been maximal in protecting the rights of the Indonesian people. To prevent the spread of Covid-19, the government asks people to keep their distance from each other, avoid crowded places such as gathering in houses of worship, markets, malls, and not to conduct events that reason many people such as weddings, meetings, and seminars. Against the steps taken by this government, many people think that it is contrary to human rights. This research method uses normative juridical approach methods with data analysis methods using qualitative data analysis. The results of this study show that government regulation should still pay attention to people's rights, such as the right to work, health, and so on. Applying the law in an emergency must be acted wisely, not to debate so that people's rights are ignored. In addition, the role of the community is also needed to remain in compliance with health protocols in a disciplined manner so that the transmission of the Covid-19 virus can be suppressed.